Peran perempuan dalam dakwah keluarga - Enung Asmaya (Yinyang: Jurnal Studi Islam Gender dan Anak, 2020)
The role of women in the family is strong and cannot be separated. Its existence is missed and even needed by the children and husband. Women (in this case mother or wife) have a strong heart relationship with children so that the leadership of women in the family cannot be ignored or avoided. However, there are still people who doubt the ability of women as da'wah leaders in the family because of the many dynamics and challenges of preaching in the family. The physical and psychological closeness of women often causes difficulties for children to be obeyed, especially when the children have bad habits. Therefore, this paper will discuss how the leadership of da'wah for women in families. The results of this study explain that women can become play a role as the manager of the family spirit, sholihah morality education, regulator of meeting daily needs and enterainers of family members.